Kinetics of stibnite (Sb2S3) oxidation at roasting temperatures - Padilla R.; Aracena A.; Ruiz M.C. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Experimental work on the oxidation of stibnite (Sb2S3) was carried out at temperatures between 350 and 500°C and oxygen partial pressures between 1.01 and 21.28 kPa by using a thermogravimetric analysis method. The oxidation rate of stibnite was significantly influenced by both temperature and partial pressure of oxygen. Stibnite oxidized in one step to valentinite (Sb2O3) and neither stibnite nor valentinite showed a detectable rate of volatilization at these low temperatures. The oxidation reaction of stibnite was analyzed by using the shrinking core model and it was found that the rate of reaction was controlled by the surface chemical reaction and it was of 3/5 order with respect to the oxygen partial pressure. The intrinsic rate constants were determined and an activation energy value of 90.3 kJ/mol was obtained for the range of temperature studied.